Improving quality of referral letters from primary to secondary care: a literature review and discussion paper. Issue 3 (7th December 2017) - Tobin-Schnittger, Patrick; O'Doherty, Jane; O'Connor, Ray; O'Regan, Andrew
Abstract : Background: Referral letters sent from primary to secondary or tertiary care are a crucial element in the continuity of patient information transfer. Internationally, the need for improvement in this area has been recognised. This aim of this study is to review the current literature pertaining to interventions that are designed to improve referral letter quality. Methods: A search strategy designed following a Problem, Intervention, Comparator, Outcome model was used to explore the PubMed and EMBASE databases for relevant literature. Inclusion and exclusion criteria were established and bibliographies were screened for relevant resources. Results: A total of 18 publications were included in this study. Four types of interventions were described: electronic referrals were shown to have several advantages over paper referrals but were also found to impose new barriers; peer feedback increases letter quality and can decrease 'inappropriate referrals' by up to 50%; templates increase documentation and awareness of risk factors; mixed interventions combining different intervention types provide tangible improvements in content and appropriateness. Conclusion: Several methodological considerations were identified in the studies reviewed but our analysis demonstrates that a combination of interventions, introduced as part of a joint package and involving peer feedback can improve.